Grand challenges in sustainable intensification and ecosystem services - Firbank, L; Attwood, S; Eory, V; Gadanakis, Y; Lynch, J; Sonnino, R; Takahashi, T (Frontiers Media, 2018)
Arguably the greatest grand challenge for humankind is to keep the biosphere within its safe and just operating space, providing sufficient resources to meet people’s needs without exceeding the Earth’s capacity to supply them (Raworth, 2012). “Safe” is defined in terms of keeping planetary environmental processes, through mechanisms such as climate regulation and improved nutrient cycles, within limits over the long term (Rockstrom et al., 2009). “Just” is increasingly being interpreted in terms of meeting the UN Sustainable Development Goals, with targets addressing various forms of equity as well as biophysical needs (Griggs et al., 2013). Keeping the biosphere within the operating space requires that we produce the food we need, along with the ecosystem and socioeconomic goods and services we require (Garnett et al., 2013). By definition, achieving this challenge also means achieving the sustainable intensification (SI) of agriculture, whereby more food is produced from the same area of land (or water), with reduced or reversed negative environmental impacts accompanied by a range of positive societal and environmental co-benefits. SI is variously considered as a goal (Royal Society, 2009), a process (Firbank et al., 2013), a trade-off between economic production activity and ecological performance (Gadanakis et al., 2015), or a suite of interventions (Godfray and Garnett, 2014).